F0 Perturbation of Stops in Nepali and Meitei - Singh, Neelam (Nepalese Linguistics, 2022)
The present article accounts for the fundamental frequency (F0) perturbation of stop-types in Nepali spoken in the Maram region of Manipur, India. Experiments were performed on the speech of the native speakers of Nepali in order to investigate if the F0 perturbation following the stop-types would be affected due to contact with a tonal language, Meitei.